(untitled) (Physical Education, Health and Social Sciences, 2025)
This systematic synthesis integrates recent literature from 2015 to 2025 to explore K-12 teachers’ professional development and the common challenges they encounter in instructing STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning. STEAM, as a combined K-12 learning approach, is conceptualized to prepare students for 21st-century workforce demands with essential learning skills; notwithstanding, successful implementation is usually hindered by systemic and pedagogical barriers. Our synthesis reveals prominent barriers, such as rigid curricula, resource constraints, insufficient preparation for interdisciplinary and intrapersonal competencies, and inconsistent administrative support. Successful methodologies, by contrast, value the potential of experiential, interdisciplinary and intrapersonal and iterative professional learning to broaden the self-efficacy of teachers, construct interdisciplinary and intrapersonal knowledge bases, and integrate technology. authentic classroom practice is invariably characterized by culturally responsive, inquiry-based, and student-centered learning environments. The synthesis provides practical recommendations for teachers, policymakers, and professional learning leaders to incorporate tailored support and adaptive structures to allow teachers to facilitate meaningful STEAM learning experiences.